2020
DOI: 10.1038/s41598-020-68237-2
|View full text |Cite
|
Sign up to set email alerts
|

Sand deposits reveal great earthquakes and tsunamis at Mexican Pacific Coast

Abstract: Globally, instrumentally based assessments of tsunamigenic potential of subduction zones have underestimated the magnitude and frequency of great events because of their short time record. Historical and sediment records of large earthquakes and tsunamis have expanded the temporal data and estimated size of these events. instrumental records suggests that the Mexican Subduction earthquakes produce relatively small tsunamis, however historical records and now geologic evidence suggest that great earthquakes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Interestingly, a day after the main earthquake, a M7.5 aftershock hit the zone; it is thought the generated tsunami affected a local fishing community with waves ranging from 2 to 3 m high [15]. More recently, it has been found that instrumentally based assessments of "tsunamigenic" possibility of subduction zones in the Pacific coast have underestimated the frequency and magnitude of great earthquakes and tsunamis [25]. The authors argue that geological evidence shows that in fact great tsunamis (and earthquakes) have occurred in the subduction zone in the past, i.e., the stretch of the coasts of Guerrero and Oaxaca, the southern region of Mexico.…”
Section: Local Tsunami Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a day after the main earthquake, a M7.5 aftershock hit the zone; it is thought the generated tsunami affected a local fishing community with waves ranging from 2 to 3 m high [15]. More recently, it has been found that instrumentally based assessments of "tsunamigenic" possibility of subduction zones in the Pacific coast have underestimated the frequency and magnitude of great earthquakes and tsunamis [25]. The authors argue that geological evidence shows that in fact great tsunamis (and earthquakes) have occurred in the subduction zone in the past, i.e., the stretch of the coasts of Guerrero and Oaxaca, the southern region of Mexico.…”
Section: Local Tsunami Riskmentioning
confidence: 99%
“…For example, it has been found evidence of two sand tsunami deposits, 1.5 km inland of the coast [25]. Further, it is believed that an earthquake of M8.6 of magnitude occurred in 1787 and produced a giant tsunami that flooded up to 6 km inland.…”
Section: Local Tsunami Riskmentioning
confidence: 99%
“…occurred in historical time and geological evidence of the 1787 and probable predecessor in 1537 have flooded the southwest coast of Mexico (Ramírez-Herrera et al, 2020). However, because of the short instrumental record, tsunami hazard has been minimized and incorrectly evaluated on the Pacific coast of México.…”
Section: Manuscript Submitted To Seismological Research Letters Manusmentioning
confidence: 99%
“…predecessor of 1537 (Ramírez-Herrera et al, 2020). Instrumental data unfortunately do not capture in their short record (ca.…”
Section: Manuscript Submitted To Seismological Research Letters Manusmentioning
confidence: 99%
See 1 more Smart Citation